Efek Perkecambahan Biji Kedelai Terhadap Viskositas, Ph, Total Padatan Terlarut, Protein Terlarut, Dan Gugus Fungsi Pada Susu Kedelai - Sukmawati Arifin, Arfina (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2023)
Soymilk is an alternative to cow's milk for lactose intolerant patients and vegetarians. In this study, soymilk was made from soybean seeds that have been germinated because it is known that the germination process can increase the nutritional value of soybean. This study aims to determine the effect of soybean germination on viscosity, pH, soluble protein, and functional groups in soymilk produced. There were five treatments of soybean used, namely soybean without soaking and germination (control), soybean soaked without germination, soybean soaked and germinated for 24 hours, 36 hours, and 48 hours. Soybean seeds were heated and then ground, filtered, and the filtrate was heated and sugar was added to obtain soymilk. The results showed that soybean germination was able to reduce viscosity and total soluble solids and increase soluble protein in the soymilk produced. In addition, N-H, C=N functional groups indicating protein, OH, C-H aromatic, C=C aromatic and C-O indicating isoflavone compounds were identified, and C=O and OH groups at 48 hours of germination which indicate carboxylic acid, thus indicating the presence of GABA compounds.